Peningkatan Pengetahuan Dengan Kesadaran Diri Terhadap Perilaku Hidup Bersih dan Sehat (PHBS) - Aristoteles Aristoteles; Anggi Restu Putri; Arifa Al Husnah; Detri Dipa Utami; Ayu Niara Kalwa; Amelda Amelda; Angel Anjelina; Ervina Rosa; Bambang Ari Anggara; Cahya Yulia Pratiwi; Citra Amelya (Indonesian Journal Publisher, 2024)
Until now, public health problems are still a concern. for the government. Public awareness of the importance of health is still low. The level of public health is uneven and very low, especially in people living in slum settlements. Clean and Healthy Living Behavior (PHBS) is a health behavior carried out with awareness, so that a person can improve their health status. Community behavior that is still unhygienic, coupled with the absence of supporting environmental facilities and infrastructure, has an impact on the health of people living in these slum settlements. Many public health problems may arise due to people's behavior and environmental conditions that do not pay attention to health. The problems found in the Silaberanti sub-district, especially in RT 26, 41 and 42, are a lack of public awareness of clean and healthy living behavior, this can be seen from an unclean environment and improper disposal of rubbish. The solution used to overcome this problem is by increasing awareness community through outreach activities about clean and healthy living behavior and working together to clean the surrounding environment. The results of this activity have a positive impact on society by providing good understanding 90% thereby increasing self-awareness of clean and healthy living behavior.